Romiplostim for secondary thrombocytopenia following allogeneic stem cell transplantation in children. - Maximova, Natalia; Zanon, D; Rovere, F; Maestro, A; Schillani, G; Paparazzo, R (Int J Hematol, 2015)
The outcome of romiplostim for secondary failure of platelet recovery (SFPR) was investigated in children who had undergone hematopoietic stem cell transplantation (HSCT). Seven transfusion-dependent pediatric patients (median age 11 years), with platelet counts below 10 × 10(9)/L, received four weekly doses of subcutaneous romiplostim to treat SFPR developed after HSCT. All patients, except one (patient 4), became platelet transfusion-independent in the second week from the beginning of treatment and no patient needed to discontinue drug treatment because of adverse events. Romiplostim could represent a beneficial first-line treatment, but further studies are required.